Media Promosi Dan Informasi Guna Penunjang Iklan Sport Party (GOFIT) PT. Arka Mahesa Pratama Jakarta - M. Ifran Sanni; Siti Maesaroh; Rifqi Baihaqi (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
PT. Arka Mahesa Pratama Jakarta at the moment still use media design or events to websites but the result of such media are still less effective so many masyakat yet mengetahiunya. PT. Arka Mahesa Pratama Jakarta desperately needs the project shaped media video ads so the public know more. On the concept of there stages of preproduction, production and postproduction. To get the maximum project then the need of supporting applications that will be used so that the end result of the work of the project video more interesting.